Social media & stem cell science: examining the discourse. (November 2011) - Adams, Amy; Lomax, Geoffrey; Santarini, Anthony
Research suggests that the representation of scientific and medical issues in the traditional media such as newspapers, TV and radio is an important determinant of public opinion and related public policy outcomes, particularly with regard to attitudes toward stem cell research. With the emergence of social media, the discursive space around public policy issues has expanded to include a new demographic of media consumer who is directly involved in political action. However, little is known about the influence of social media on scientific public policy conversations. We analyzed Twitter posts on two topics relating to stem cell science and policy according to the originator and tone of the tweet, and whether the tweet was intended to be neutral or to further a stated policy position. This analysis provides a means for clarifying the role of social media in influencing public opinion of policy issues such as stem cell research and offers organizations a better understanding of how to more effectively apply social media to advancing their stem cell policy positions.